Disease phenotypic and outcome of very-early onset inflammatory bowel disease in Asian children: an understudied population - Lee, Way-Seah; Chew, Kee-Seang; Huang, James-Guoxian; Tanpowpong, Pornthep; Mercado, Karen S. C.; Reodica, Almida; Logarajah, Veena; Hathagoda, K. L. W.; Rajindrajith, Shaman; Wong, Yoko Kin-Yoke; Treepongkaruna, Suporn; Aw, Marion Margaret (Frontiers in Pediatrics, 2025)
BackgroundThere is a paucity of knowledge on disease phenotype and outcome of very early-onset (VEO) inflammatory bowel disease (VEO-IBD) from recently developed and developing countries, including from Southeast Asia. We studied disease phenotype, clinical characteristics, management and outcome of VEO-IBD in South and Southeast Asian children.Materials and methodsWe extracted data from a multicentre Asian pediatric (onset <18 years) IBD registry. VEO- and later-onset pediatric (LO-p) IBD were defined as onset of disease <6 years and ≥6 years, respectively. We excluded monogenic IBD.ResultsOf 440 children with IBD cases; 112 (25.5%) were VEO-IBD; Crohn's disease (CD) 36 (32.1%); ulcerative colitis (UC) 68 (60.7%), and IBD-unspecified 7 (7.1%). UC was more common in VEO-IBD while CD more common in LO-pIBD (CD = 68.9% vs. UC = 25.9%; p < 0.001). Disease location/extent of disease and disease severity were similar in both age groups for both CD and UC. For CD, inflammatory disease behavior was equally common in both age group (77.8% in VEO-IBD vs. 76.6% of LO-pIBD), majority had isolated colonic disease (27.8% VEO-IBD vs. 36.3% LO-pIBD), while stricturing and penetrating diseases were not observed in VEO-CD, but noted in 4.9% and 8.4% of LO-pCD, respectively. Among UC cases, pancolitis was observed in 60.3% of VEO-IBD vs. 65.9% of LO-pIBD. Most UC never had severe disease regardless of age group. Five years after diagnosis, VEO-IBD were more likely to have corticosteroids, immunomodulators or biologics than LO-pIBD. Despite this, inactive/mild disease activity was the predominant outcome at 5 year follow up for both VEO-CD (98.2%) and VEO- UC (96.1%). Bowel surgery rate was 2.4% and 1.7% for VEO- and LO-IBD at 5 years, respectively.ConclusionsDespite differences in disease phenotype at diagnosis, disease behaviour, location/extent and disease severity were similar between VEO- and LO-IBD, with a comparable overall clinical remission rates between both age groups at 5 years after diagnosis.